Genetic ancestry of the Mulam ethnic group: admixture from ancient Yellow River, southern native, and Austronesian populations - Wendi Dang; Xiaoming Wu; Jing Zhao; Song Lin; Xirui Wang; Xiaomin Yang; Jin Sun; Tielin Yang; Chuan-Chao Wang; Hu-Qin Zhang (Human Genetics, 2026)

Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Vision-based autonomous leaf-level spraying using wrist-inspired manipulators for integrated pest management in papaya greenhouses - Nhu Tuong An Nguyen; Dang Khanh Linh Le; Wei-Chih Lin (Computers and Electronics in Agriculture, 2026)

Treatment of nitrogen micro-polluted wastewater using a new type of biological folded non-aerated filter (BFNAF): Performance, microbial community and machine learning optimization - Jie Han; Youzhao Wang; Mingdong Chang; Xiaoyan Dang; Shumin He; Xiaodi Huang; Yongguang Ma; Zhipeng Wang; Yaonan Zhu; Junnan Liu; Jinxiang Wang; Lin Zhai; et al. (Journal of Environmental Chemical Engineering, 2026)

Continuous flow-through electrochemical pretreatment for fouling control in ultrafiltration-based wastewater reclamation - Weichen Zeng; Yunan Gao; Dachao Lin; Hongyan Sun; Diannan Huang; Xueding Jiang; Zhi Dang; Hailong Wang (Chemical Engineering Journal, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Biodegradation of cyano liquid crystal monomers by an aerobic enrichment culture: Key degraders and interspecies synergistic mechanisms - Minghan Zhu; Chang He; Shaoyu Tang; Jiayu Zhang; Zhen Yu; Hui Lin; Yibo Yuan; Jonathan W.C. Wong; Hua Yin; Junfeng Niu; Xujun Liang; Zhi Dang (Water Research, 2026)

Phenotypic and molecular characterization of Vibrio cholerae from aquatic products - Yao Shen; Jiangang Ma; Huafeng Jian; Shuaijie Song; Zhiyu Li; Fengcheng Miao; Xiaoqian Long; Yukun Jie; Yuchen Wang; Feng Lin; Yali Dang; Hua Yang (Journal of Invertebrate Pathology, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Dynamic response of heterogeneously stratified calcareous sand foundations: An integrated experimental-numerical study - Jun Hu; Mengyi Liu; Shuai Zhang; Hanyu Dang; Mingren Lin; Yu Li (Marine Georesources & Geotechnology, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

Corrigendum to “Phenotypic and molecular characterization of vibrio cholerae from aquatic products” [J. Invertebr. Pathol. 218 (2026) 108644] - Yao Shen; Jiangang Ma; Huafeng Jian; Shuaijie Song; Zhiyu Li; Fengcheng Miao; Xiaoqian Long; Yukun Jie; Yuchen Wang; Feng Lin; Yali Dang; Hua Yang (Journal of Invertebrate Pathology, 2026)

Sonar-Based Seepage Detection and Hydro-Thermal Modelling of Frozen Soil Curtain Evolution for Subway Cross-Passages in High-Permeability Strata - Shengbin Hu; Hang Lin; Jun Hu; Bafeng Ren; Xiaofeng Song; Zhuang Hu; Hanyu Dang (Geotechnical and Geological Engineering, 2026)

Organophosphate triesters and diesters in the Yellow River Basin (Shandong section): Geographical patterns, land use correlates and compound-specific source apportionment - Yuting Ren; Lin Zhu; Huijie Dang; Lili Cui; Ang Zhao; Chao Wei; Mei Wang (Marine Pollution Bulletin, 2026)

Efficient phosphate removal and flocculation of Microcystis aeruginosa via a flower-like spherical Metal-Organic Framework La-BDC-NH2: Investigation of performance and mechanism - Jinyun Guan; Dandan Wang; Xiaozheng Ma; Ruoxin Wang; Lin Dang; Yihang Sun; Yichenyang Li; Jifeng Guo (Chemical Engineering Journal, 2026)

Robust, thermal insulated cellulose porous films for durable and efficient radiative cooling - Xinxin Chen; Mengxiang Dang; Longfei Sun; Yusong Xu; Yu Liu; Lin Liu; Guocheng Zhu; Juming Yao (Carbohydrate Polymers, 2026)

Study on the effect of heating and cooling paths on the macro- and micro-properties of red sandstone based on low-field NMR - Shuang Dang; Lin Ning; Jing Bi; Yu Zhao; Yuhang Zhao; Chaolin Wang; Zhongqian Chen (Bulletin of Engineering Geology and the Environment, 2026)

Microbial metabolism regulates the stabilization of rhizodeposition-derived carbon in soil aggregates and mineral fractions under long-term tillage - Wen-Sheng Liu; Ben-Shun Liu; Zi-Ang Wang; Yong-Qiang Xu; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2026)

Wave forces of subsea cables laid on meso-scale rough seabeds - Zhe Gao; Dang Zhao; Yunfei Teng; Yuanyuan Xu; Liang Cheng; Guoqiang Tang; Lin Lu; Dongsheng Qiao (Ocean Engineering, 2026)

Biopolymer-based edible film incorporating Melaleuca Bracteata F. Muell. Essential oil with antimicrobial and antioxidant properties: A promising approach for strawberry fruit preservation - Jinjie Yang; Yaqian Niu; Penghui Hu; Yunqing Song; Ruihan Dang; Linke Li; Yuke Zhang; Yanshu Gong; Yixuan Lin; Ying Xin (Food Research International, 2026)

Dissolved organic matter inhibit the degradation process of polystyrene nanoplastic under utraviolet light - Si-Jia Liu; Jing-Jing Yang; Wei-Lin Huang; Ting-Ting Cai; Jing-Yi Gu; Zhi Dang; Chen Yang (Water Research, 2026)

Chicken sternum cartilage protein-chelated calcium: enhance bone density in vivo and in vitro, with insights into chelation mechanism - Shikun Suo; Yanli Wang; Lihui Du; Maolin Tu; Kuo Dang; Jingyi Chen; Yi Lin; Yali Dang; Qingqing Li (Food Research International, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

Lattice distortion-driven electronic engineering of high-entropy alloys for efficient polysulfide catalysis in LiS batteries - Li Zhang; Yan Wang; Bo-Wen Lin; Rong-Rong Liang; Tian-Hui Dang; Zhuo Zhao (Chemical Engineering Journal, 2026)

Repairing osteoporotic bone defects under iron overload: A chitosan-hyaluronic acid hydrogel via synergistic iron chelation and ROS responsiveness - Tong Lin; Ziyi He; Tianhao Zhao; Qiaochu Fan; Ruibo Hu; Junhui Jiang; Junbo Dang; Mei Zhang; Dahui Sun (Carbohydrate Polymers, 2026)

Toward a resilience-oriented ecological network for the Loess Plateau - Yuan Wang; Zhihui Lin; Hui Dang; Zhuangzhuang Wang; Xianfeng Liu (Applied Geography, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

Carbon mineralization and temperature sensitivity of particulate versus mineral associated organic matter in a 56-year long-term no-till Vertisol - Cong He; Ram C. Dalal; Tong Li; Hai-Lin Zhang; Yash Pal Dang (Agriculture, Ecosystems & Environment, 2026)

Synergistic effect of above- and belowground short-term recovery in alpine meadows driven by grass debris mulching - Lingchao Meng; Shangyin Deng; Zhiqiang Dang; Jingxue Zhao; Manuel López-Vicente; Gao-Lin Wu (Agriculture, Ecosystems & Environment, 2026)

Improving soil organic carbon sequestration through conservation tillage incorporating legume-based crop rotations - Wen-Xuan Liu; Zhuo Shi; Hai-Yan He; Bai-Jian Lin; Cong He; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Soil and Tillage Research, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Simultaneous stabilization of As/Pb and enhancement of nitrogen retention in farmland soil by the novel Fe-Mn oxidizing bacteria co-inoculation - Xiaofang Ouyang; Zhanyu Guo; Lin Bian; Zhi Dang; Meiying Xu; Hua Yin (Journal of Hazardous Materials, 2026)

Synergy between monomer oxygen vacancies and oxygen vacancy clusters in MnO2 enables efficient catalytic decomposition of N2O - Hui Dang; Wanjun Zhao; Chengming Zhang; Ruifang Wu; Liangliang Zhang; Ke Zheng; Shize Hu; Xiangqian Lin; Aiping Jia; Zhenxing Ren; Yongzhao Wang; Yongxiang Zhao (Journal of Hazardous Materials, 2026)

A 13C-PLFA approach to assess the crop carbon allocation efficiency and arbuscular mycorrhizal assimilation capacity under conservation tillage - Wen-Sheng Liu; Shuo Yao; Zhuo-Jun Lin; Olatunde Pelumi Oladele; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Biology and Fertility of Soils, 2026)

Intercropping maize and soybean promotes specialized soil microbial communities and boosts carbon and nitrogen cycling in a semi-arid agroecosystem - Olatunde Pelumi Oladele; Shuo Yao; Ming-Zhu Huang; Yu-Gang Tian; Xin Zhao; Yash Pal Dang; Wei Bai; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Diversification and differentiation of Stipa species shed light on the regional evolutionary history of the eastern Eurasian steppe - Dongqing Yan; Yanyan Fan; Xiaoru Jiang; Yang Ma; Kejian Lin; Zhenhua Dang; Jianming Niu (Molecular Phylogenetics and Evolution, 2025)

Spatial heterogeneity and nonlinear relationship between landscape ecological risk and drivers: a case of the Qinghai-Tibet Plateau, China - Fazi Zhang; Jingyao Lin; Qiang Wang; Yuying Lin; Niu Dang; Yinan Li (Environment, Development and Sustainability, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Insights into the occurrence of ten bisphenol analogues in tidal flat and deepwater sediments in the Pearl River Basin - Jin-yi Sun; Ze-hua Liu; Can-yuan Lin; Jian Gong; Zhi Dang (Environmental Pollution, 2025)

Design and characterization of AgC nanocomposite frameworks in porous silicon anodes for high-performance solid-state batteries - Baoguo Zhang; Lin Wu; Xiaoyu Yang; Jingwang Li; Zefeng Yuan; Zihao Dang; Rongsheng Chen; Ying Liu; Ya Hu (Chemical Engineering Journal, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Quantitative prediction and mechanistic insights into Cu(II) transport in kaolinite-coated sand columns affected by ferrihydrite nanoparticles - Lijuan Zeng; Guining Lu; Feng Jiang; Ying-Jie Zhang; Xiaohu Jin; Weilin Huang; Yu-Jung Lin; Jyh-Fu Lee; Xiaoyun Yi; Zhi Dang (Journal of Hazardous Materials, 2025)

Simultaneous detection of 12 estrogens in poultry meat and blood via ultrasonic extraction and GC–MS: Implications for emerging hormone exposure and health risk assessment - Can-yuan Lin; Ze-hua Liu; Dong-hao Luo; Xiao-zhan Wang; Jian Gong; Jin-yi Sun; Zhi Dang (Food Chemistry, 2025)

Comprehensive assessment of natural estrogens in poultry eggs: Implications for health risks and dietary intervention strategies - Can-yuan Lin; De-ming Kong; Jian Gong; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Jin-yi Sun (Food and Chemical Toxicology, 2025)

Widespread microplastic and nanoplastic contamination in the intestines of birds: A case study from Chengdu, China - Pinxi Zhou; Mengzhu Wang; Shane DuBay; Yiwei Cao; Shangmingyu Zhang; Jiayu Zhang; Zhengrui Hu; Zhixiong Yang; Yibo Wang; Xiaoying Zhao; Lin Sun; Jiachen Dang; et al. (Journal of Hazardous Materials, 2025)

The competitive effects of crop straw return and nitrogen fertilization on soil acidification - Jia Cheng; Cheng-Ze Yang; Le Zhang; Zhuo-Jun Lin; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Corrigendum to “Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan” [J. Hydrol. 649 (2025) 132450] - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Responses of soil physical and chemical properties to degradable and non-degradable microplastics - Hongjia Peng; Lawei Dang; Zuhong Lin; Bolun Yu; Haipu Li; Jingjing Yao (Journal of Environmental Chemical Engineering, 2025)

Stability and Adaptability of Sugar Beet Examined Based on AMMI and BLUP–GGE Biplot Analyses - Yuhang Lin; Xinwang Dang; Xiaohang Hu; Yanli Li; Shuo Liu (Sugar Tech, 2025)

A state-of-the-art empirical round robin validation of heat, air and moisture (HAM) models - Xinyuan Dang; Ana Sofia Guimarães; Andreas Sarkany; Anssi Laukkarinen; Bingyu Xu; Bruno Vanderschelden; Carsten Rode; Changchang Xia; Chi Feng; Chris Whitman; Daan Deckers; Hanyu Yang; et al. (Building and Environment, 2025)

Flow analysis and fate of mercury in Chinese polyvinyl chloride production - Dandan Liu; Gang Fang; Yuchen Lin; Fan Wang; Zixiu Li; Chunge Dang (Process Safety and Environmental Protection, 2025)

Differential microbial degradation of cross-linked Polythene by Aspergillus niger in space and on the ground - Shuyuan Zhang; Lei Dang; Weiliang Li; Qin Zhang; Kui Xiao; Tong Tong; Qianqian Liu; Lingling Ma; Nana Chen; Lantao Zhang; Yali Feng; Yan Song; et al. (Chemical Engineering Journal, 2025)

Impact of Energy Transition on CO2 Emissions in China’s Cities - Niu Dang; Qiang Wang; Mei-po Kwan; Jian Lin (Chinese Geographical Science, 2025)

Establishment of an inter-provincial compensation system for farmland protection in China: A framework from zoning-integrative transferable development rights - Zhen Xie; Xiaorui Lin; Chun Jiang; Yuxuan Dang; Xiangbin Kong; Chenyu Lin (Land Use Policy, 2025)

Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Pseudostellaria heterophylla cultivar mixtures driven changes in rhizosphere metabolites to suppress soil-borne Fusarium disease - Yuting Liu; Yixuan Zhang; Xingyue Wang; Panpan Dang; Antonino Malacrinò; Jiaoyang Zhang; Zhong Li; Christopher Rensing; Zhongyi Zhang; Wenxiong Lin; Zhen Zhang; Hongmiao Wu (Agriculture, Ecosystems & Environment, 2025)

Unraveling carbon mineralization patterns and mechanisms in conservation agriculture: A global synthesis and multi-point experiment - Cong He; Jin-Sai Chen; Shou-Wei Han; Wen-Sheng Liu; Wen-Xuan Liu; Olatunde Pelumi Oladele; Yash Pal Dang; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Journal of Cleaner Production, 2025)

Enhancing soil ecosystem multifunctionality through combined conservation tillage and legume-based crop rotation in the North China Plain - Wenxuan Liu; Cong He; Shouwei Han; Baijian Lin; Wensheng Liu; Yash Pal Dang; Xin Zhao; Hailin Zhang (Agriculture, Ecosystems & Environment, 2025)

Evaluation of PM2.5 bound microplastics and plastic additives in several cities in Taiwan: Spatial distribution and human health risk - Chien-Hsing Wu; Tuan Truong Minh Dang; Justus Kavita Mutuku; Li-Man Lin; Bo-Wun Huang; Guo-Ping Chang-Chien (Science of The Total Environment, 2025)

Strategies for crop straw management in China's major grain regions: Yield-driven conditions and factors influencing the effectiveness of straw return - Jia Cheng; Bai-Jian Lin; Jin-Sai Chen; Hong-Xuan Duan; Yuan-Feng Sun; Xin Zhao; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2025)

Molecular phylogenetic and estimation of evolutionary divergence and biogeography of the family Schizoparmaceae and allied families (Diaporthales, Ascomycota) - Taichang Mu; Yongsheng Lin; Huili Pu; Nemat O. Keyhani; Yuxiao Dang; Huajun Lv; Zhiying Zhao; Zhiang Heng; Ziyi Wu; Chengjie Xiong; Longbing Lin; Yuxi Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Integrated deep banding and fertigation of phosphorus improves cotton yield by regulating root spatial distribution and growth - Zheng He; Xuwei Dang; Gaifang gao; Xinyuan Lin; Fuyu Ma; Yang Liu (Field Crops Research, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Livestock grazing modes induced the rapid differentiation of community recruitment in alpine meadow - Hui Fang; Lingchao Meng; Zhiqiang Dang; Jingxue Zhao; Shixiong Li; Gao-Lin Wu (Ecological Engineering, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Optimizing straw and nitrogen fertilizer resources for low-carbon sustainable agriculture - Bai-Jian Lin; Jia Cheng; Hong-Xuan Duan; Wen-Xuan Liu; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Resources, Conservation and Recycling, 2024)

Combining base to topdressing ratio and layered application of phosphorus fertilizer enhanced cotton yield by regulating root distribution and activity - Zheng He; Xuwei Dang; Xinyuan Lin; Gaifang Gao; Yang Liu; Fuyu Ma (Soil and Tillage Research, 2024)

Straw returning and nitrogen reduction: Strategies for sustainable maize production in the dryland - Miaomiao Zhang; Ning Yang; Shiguang Wang; Xiaoqing Han; Pengfei Dang; Guoqing Li; Shuyue Wen; Lin Zhang; Jiquan Xue; Xiaoliang Qin; Kadambot H.M. Siddique (Journal of Environmental Management, 2024)

Retraction Note: Role of energy consumption and sustainability-oriented eco-innovation on economic growth: evidence from Middle Eastern economy - Yu-Te Tu; Chia-Yang Lin; Syed Ehsanullah; Nguyen Ho Viet Anh; Khoa Dang Duong; Pham Quang Huy (Environmental Science and Pollution Research, 2024)

Baicalin attenuates acute skin damage induced by ultraviolet B via inhibiting pyroptosis - Zuohao Liu; Bingrong Dang; Zhen Li; Xingsheng Wang; Yuhan Liu; Fen Wu; Xinhui Cao; Chunming Wang; Changjun Lin (Journal of Photochemistry and Photobiology B: Biology, 2024)

Low temperature acclimation of electroactive microorganisms may be an effective strategy to enhance the toxicity sensing performance of microbial fuel cell sensors - Yazhi Nong; Min Xu; Bingchuan Liu; Jianfeng Li; Dongye He; Chuanfu Li; Pinyi Lin; Yin Luo; Chenyuan Dang; Jie Fu (Water Research, 2024)

Optimizing the rate of straw returning to balance trade-offs between carbon emission budget and rice yield in China - Ruo-Chen Li; Yu-Gang Tian; Fan Wang; Yuan-Feng Sun; Bai-Jian Lin; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang; Zhi-Yu Xu (Sustainable Production and Consumption, 2024)

The role of C18 fatty acids in improving the digestion and retrogradation properties of highland barley starch - Mengzi Nie; Jiaxin Li; Ran Lin; Xue Gong; Bin Dang; Wengang Zhang; Xijuan Yang; Lili Wang; Fengzhong Wang; Li-Tao Tong (Food Research International, 2024)

Effect of High Magnesium and Astragaloside IV on Vascular Endothelial Cells - Hongfei Qi; Teng Ge; Kun Wang; Jing Wang; Lin Dang; Juane Li; Haifang Wang (Cell Biochemistry and Biophysics, 2024)

Efficient removal of heavy metals from acid mine drainage by ε-MnO2 adsorption - Yuebei Yang; Yaozhong Wang; Chao Xue; Yujung Lin; Jyh-Fu Lee; Xiaoyun Yi; Zhi Dang (Journal of Cleaner Production, 2024)

Human-exoskeleton cooperation for reducing the musculoskeletal load of manual handling tasks in orchid farms - Dang Khanh Linh Le; Wei-Chih Lin (Computers and Electronics in Agriculture, 2024)

Estimation of crop residue production and its contribution to carbon neutrality in China - Xin Zhao; Ruo-Chen Li; Wen-Xuan Liu; Wen-Sheng Liu; Ying-Hao Xue; Ren-Hua Sun; Yu-Xin Wei; Zhe Chen; Rattan Lal; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

New solution for predicting the removal efficiency of organic contaminants by UV/ H2O2: From a case study of 1H-benzotriazole - Juan Dang; Ling Lin; Li-ao Gao; Lin Qi; Shi-bo Zhang; Qing-zhu Zhang; Shuai Tian (Science of The Total Environment, 2024)

Examining spatial dynamics and interactions of planted alien, native, and invasive alien species in China’s largest artificial mangrove forest - Kai Liu; Yuanhui Zhu; Xuewei Dang; Soe W. Myint; Lin Liu; Jingjing Cao (Forest Ecology and Management, 2024)

Progress and evolution of hotspots in butterfly diversity research in green spaces - Ying Lin; Shanjun Huang; Wenqiang Fang; Shiyuan Fan; Chengyu Ran; Emily Dang; Weicong Fu; Zhipeng Zhu (Environmental Science and Pollution Research, 2024)

Rare earth dissolution from polishing powder waste in H2O2-H2SO4 system: Condition optimization and leaching mechanism - Lin Chen; Xiaofeng He; Xiaona Dang; Xingcang Wang; Weifeng Liu; Duchao Zhang; Tianzu Yang (Hydrometallurgy, 2024)

Deeply analyzing dynamic fermentation of highland barley vinegar: Main physicochemical factors, key flavors, and dominate microorganisms - Yan Li; Aixia Wang; Bin Dang; Xijuan Yang; Mengzi Nie; Zhiying Chen; Ran Lin; Lili Wang; Fengzhong Wang; Li-Tao Tong (Food Research International, 2024)

High-yield and scalable cellulose nanomesh preparation via dilute acid vapor and enzymatic hydrolysis-mediated nanofabrication - Xiaowen Li; Zhongrun Xiang; Wanting Dang; Zewan Lin; Huai Wang; Huiqing Wang; Dongdong Ye; Risheng Yao (Carbohydrate Polymers, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Planktonic/benthic Bathyarchaeota as a “gatekeeper” enhance archaeal nonrandom co-existence and deterministic assembling in the Yangtze River - Shufeng Liu; Yahsuan Lin; Tang Liu; Xuming Xu; Jiawen Wang; Qian Chen; Weiling Sun; Chenyuan Dang; Jinren Ni (Water Research, 2023)

Association between Asbestos Exposure and the Incidence of Kidney Cancer: a Weight-of-Evidence Evaluation and Meta-analysis - Fu-Shiuan Whitney Lee; Yu-Han Chen; Ngoc Dang Tran; Cheng-Kuan Lin; Le An Pham (Current Environmental Health Reports, 2023)

Two-stage electric vehicle charging optimization model considering dynamic virtual price-based demand response and a hierarchical non-cooperative game - Hongyu Lin; Jialu Dang; Haowei Zheng; Lujin Yao; Qingyou Yan; Shenbo Yang; Hongzhen Guo; Amjad Anvari-Moghaddam (Sustainable Cities and Society, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Enhanced arsenic(III) sequestration via sulfidated zero-valent iron in aerobic conditions: Adsorption and oxidation coupling processes - Haiming Cai; Xiaodong Du; Ziting Lin; Xueqin Tao; Mengyao Zou; Jingyong Liu; Lijuan Zhang; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2023)

Conservation tillage increases surface soil organic carbon stock by altering fungal communities and enzyme activity - Wen-Sheng Liu; Yu-Xin Wei; Ping-Ping Deng; Olatunde Pelumi Oladele; Yves N’Dri Bohoussou; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2023)

Effect of salinity stress on nitrogen and sulfur removal performance of short-cut sulfur autotrophic denitrification and anammox coupling system - Xiang Li; Yan Yuan; Pengze Dang; Bo-lin Li; Yong Huang; Wei Li; Mao Zhang; Miao Shi; Ziqi Shen; Linyan Xie (Science of The Total Environment, 2023)

A coupled electrochemical process for schwertmannite recovery from acid mine drainage: Important roles of anodic reactive oxygen species and cathodic alkaline - Ziyuan Huang; Huanxin Ma; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Xiaoyun Yi; Zhi Dang; Chunhua Feng (Journal of Hazardous Materials, 2023)

Effects of conservation agriculture on carbon mineralization: A global meta-analysis - Cong He; Zhe Chen; Ke-Yi Qiu; Jin-Sai Chen; Yves N'Dri Bohoussou; Yash Pal Dang; Hai-Lin Zhang (Soil and Tillage Research, 2023)

Effect of biomass retention time on performance and fouling of a stirred membrane photobioreactor - Bao-Trong Dang; Xuan-Thanh Bui; Thanh-Tin Nguyen; Huu Hao Ngo; Long D. Nghiem; Ky-Phuong-Ha Huynh; Thi-Kim-Quyen Vo; Thi-Dieu-Hien Vo; Chitsan Lin; Shiao-Shing Chen (Science of The Total Environment, 2023)

A chromosome-level genome assembly reveals that a bipartite gene cluster formed via an inverted duplication controls monoterpenoid biosynthesis in Schizonepeta tenuifolia - Chanchan Liu; Samuel J. Smit; Jingjie Dang; Peina Zhou; Grant T. Godden; Zheng Jiang; Wukun Liu; Licheng Liu; Wei Lin; Jinao Duan; Qinan Wu; Benjamin R. Lichman (Molecular Plant, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Remediation performance and mechanisms of Cu and Cd contaminated water and soil using Mn/Al-layered double oxide-loaded biochar - Pengcheng Lin; Hang Liu; Hua Yin; Minghan Zhu; Haoyu Luo; Zhi Dang (Journal of Environmental Sciences, 2023)

Design of solar evaporator with well-aligned and multi-scale fluid channels based on convection tuning for stable and efficient brine desalination - Chenyang Dang; Xingtian Zhang; Lin Huang; Guiyin Xu; Li Gu; Xuebo Cao; Meifang Zhu (Desalination, 2023)

RETRACTED ARTICLE: Role of energy consumption and sustainability-oriented eco-innovation on economic growth: evidence from Middle Eastern economy - Yu-Te Tu; Chia-Yang Lin; Syed Ehsanullah; Nguyen Ho Viet Anh; Khoa Dang Duong; Pham Quang Huy (Environmental Science and Pollution Research, 2023)

The characteristics of ambient air quality in urban forest areas and other urban areas of Fuzhou city, China - Weicong Fu; Yuxuan Qiao; Chenxi Que; Hongkui Chen; Emily Dang; Jianwen Dong; Shuangyi Lin (Environment, Development and Sustainability, 2022)

Biochemical and structural characterization of the cyanophage‐encoded phosphate‐binding protein: implications for enhanced phosphate uptake of infected cyanobacteria - Fangxin Zhao; Xingqin Lin; Kun Cai; YongLiang Jiang; Tianchi Ni; Yue Chen; Jianrong Feng; Shangyu Dang; Cong‐Zhao Zhou; Qinglu Zeng (Environmental Microbiology, 2022)
Summary To acquire phosphorus, cyanobacteria use the typical bacterial ABC‐type phosphate transporter, which is composed of a periplasmic high‐affinity phosphate‐binding protein PstS and a channel formed by two transmembrane proteins PstC and PstA. A putative pstS gene was identified in the genomes of cyanophages that infect the unicellular marine cyanobacteria Prochlorococcus and Synechococcus . However, it has not been determined whether the cyanophage PstS protein is functional during infection to enhance the phosphate uptake rate of host cells. Here we showed that the cyanophage P‐SSM2 PstS protein was abundant in the infected Prochlorococcus NATL2A cells and the host phosphate uptake rate was enhanced after infection. This is consistent with our biochemical and structural analyses showing that the phage PstS protein is indeed a high‐affinity phosphate‐binding protein. We further modelled the complex structure of phage PstS with host PstCA and revealed three putative interfaces that may facilitate the formation of a chimeric ABC transporter. Our results provide insights into the molecular mechanism by which cyanophages enhance the phosphate uptake rate of cyanobacteria. Phosphate acquisition by infected bacteria can increase the phosphorus contents of released cellular debris and virus particles, which together constitute a significant proportion of the marine dissolved organic phosphorus pool.

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Advanced Treatment Technologies for the Removal of Organic Chemical Sunscreens from Wastewater: a Review - ‬Huu-Tuan Tran; Bao-Trong Dang; Le Thi Thu Thuy; Hong-Giang Hoang; Xuan-Thanh Bui; Van-Giang Le; Chitsan Lin; Minh-Ky Nguyen; Kim-Qui Nguyen; Phuong-Thao Nguyen; Quach An Binh; Thi-Phuong Thuy Bui (Current Pollution Reports, 2022)

Proteomic characterization of four subtypes of M2 macrophages derived from human THP-1 cells - Pengfei Li; Chen Ma; Jing Li; Shanshan You; Liuyi Dang; Jingyu Wu; Zhifang Hao; Jun Li; Yuan Zhi; Lin Chen; Shisheng Sun (Journal of Zhejiang University-SCIENCE B, 2022)

Bacterial Communities in Coral Offspring Vary Between in situ and ex situ Spawning Environments - Jia-Ho Shiu; Che-Hung Lin; Aziz Jabir Mulla; Viet Do Hung Dang; Chia-Ling Fong; Yoko Nozawa (Frontiers in Marine Science, 2022)
Examining the bacterial communities of offspring is key to understanding the establishment of coral-bacteria associations. Although high sensitivity to the environment is expected, previous studies have only examined bacterial communities of coral offspring in ex situ (laboratory) environments, not in in situ (field) environments. Here, we examined and compared the effect of ex situ and in situ environments on bacterial communities of newly released offspring (eggs and larvae) and their maternal colonies in two phylogenetically distant coral species with different reproductive modes: Dipsastraea speciosa (Scleractinia; spawner) and Heliopora coerulea (Octocorallia; brooder). Our results demonstrated that the spawning environments do not affect the bacterial composition in maternal colonies, but influence that of the offspring (eggs of D. speciosa and larvae of H. coerulea ). Dominant bacterial operational taxonomic units (OTUs) varied between in situ and ex situ environments in the eggs of D. speciosa . The composition of bacterial communities among larvae of H. coerulea samples was more diverse in in situ environments than in ex situ environments. This study provides the first information on in situ bacterial communities in coral eggs and larvae and highlights their sensitivities to the local environment. Future studies must take into consideration the influence of ex situ environments on bacterial communities in coral offspring.

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Mechanisms of soil organic carbon stability and its response to no‐till: A global synthesis and perspective - Zheng‐Rong Kan; Wen‐Xuan Liu; Wen‐Sheng Liu; Rattan Lal; Yash Pal Dang; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2022)
Mechanisms of soil organic carbon (SOC) stabilization have been widely studied due to their relevance in the global carbon cycle. No‐till (NT) has been frequently adopted to sequester SOC; however, limited information is available regarding whether sequestered SOC will be stabilized for long term. Thus, we reviewed the mechanisms affecting SOC stability in NT systems, including the priming effects (PE), molecular structure of SOC, aggregate protection, association with soil minerals, microbial properties, and environmental effects. Although a more steady‐state molecular structure of SOC is observed in NT compared with conventional tillage (CT), SOC stability may depend more on physical and chemical protection. On average, NT improves macro‐aggregation by 32.7%, and lowers SOC mineralization in macro‐aggregates compared with CT. Chemical protection is also important due to the direct adsorption of organic molecules and the enhancement of aggregation by soil minerals. Higher microbial activity in NT could also produce binding agents to promote aggregation and the formation of metal‐oxidant organic complexes. Thus, microbial residues could be stabilized in soils over the long term through their attachment to mineral surfaces and entrapment of aggregates under NT. On average, NT reduces SOC mineralization by 18.8% and PE intensities after fresh carbon inputs by 21.0% compared with CT ( p Q 10 ) is observed in NT due to greater Q 10 in macro‐aggregates, an increase of soil moisture regime in NT could potentially constrain the improvement of Q 10 . This review improves process‐based understanding of the physical and chemical mechanism of protection that can act, independently or interactively, to enhance SOC preservation. It is concluded that SOC sequestered in NT systems is likely to be stabilized over the long term.

Evaluation of three common alkaline agents for immobilization of multi-metals in a field-contaminated acidic soil - Zhiliang Li; Yanyan Gong; Dongye Zhao; Zhi Dang; Zhang Lin (Environmental Science and Pollution Research, 2021)

GABA Signaling Pathway-associated Gene PLCL1 Rare Variants May be Associated with Autism Spectrum Disorders - Fengyun Zheng; Guoyuan Liu; Ting Dang; Qiaowen Chen; Yu An; Meng Wu; Xiangxuan Kong; Zilong Qiu; Bai-Lin Wu (Neuroscience Bulletin, 2021)

Spatial-Temporal Change of Phytoplankton Biomass in the East China Sea with MODIS Data - Yumei Wu; Haopeng Zhu; Xiaoyan Dang; Tianfei Cheng; Shenglong Yang; Lin Wang; Liangmin Huang; Xuesen Cui (Journal of Ocean University of China, 2021)

The impact of meteorological conditions on Air Quality Index under different urbanization gradients: a case from Taipei - Zhipeng Zhu; Yuxuan Qiao; Qunyue Liu; Conghua Lin; Emily Dang; Weicong Fu; Guangyu Wang; Jianwen Dong (Environment, Development and Sustainability, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Sea Urchins Play an Increasingly Important Role for Coral Resilience Across Reefs in Taiwan - Viet D. H. Dang; Pak-Yin Cheung; Chia-Ling Fong; Aziz J. Mulla; Jia-Ho Shiu; Che-Hung Lin; Yoko Nozawa (Frontiers in Marine Science, 2020)
Herbivores are an important functional group that control algae, create new space, and promote recruitment for coral recovery. However, on many coral reefs, overfishing has greatly decreased the density of herbivores, especially fishes and gastropods, impairing coral resilience. On such overfished reefs, remnant herbivores that are not target species of local fisheries, e.g., sea urchins, are expected to play an increasingly important role, yet few studies, except for those in the Caribbean and Kenya have examined non-fish herbivores in relation to coral resilience. Here, we conducted field surveys at 30 sites along three coral reefs in Taiwan between 2016 and 2017, to examine the relative importance of six key factors for coral resilience: herbivore abundance (fishes, gastropods, sea urchins), coral cover, macroalgal cover, habitat complexity, water depth, and wave exposure. The density of juvenile coral was used as a proxy of coral resilience. Diadematid sea urchins ( Echinothrix spp. and Diadema spp.) dominated most sites (19 of 30 sites) and multivariable regression models showed sea urchin density as the best positive predictor of coral juvenile density. The results elucidated the increasing role diadematid sea urchins play as remnant herbivores on overfished coral reefs in Taiwan. Given that overfishing is a widespread issue, this phenomenon may be occurring globally. More studies are needed to examine the role of remnant, but often ignored, sea urchin herbivory on coral resilience. Reef managers should consider monitoring locally remnant herbivores and incorporating them into management strategies.

An allotriploid hybrid developed from a female 2n gamete was obtained from Eriobotrya japonica (Thunb.) Lindl × E. deflexa (Hemsl.) Nakai - Yanjuan Song; Jiangbo Dang; Weiwei Chen; Guo Wen; Qiao He; Xiaolin Li; Shoukai Lin; Guolu Liang; Qigao Guo (Euphytica, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

US antidumping petitions and revealed comparative advantage of shrimp‐exporting countries - Chia‐Lin Chang; Michael McAleer; Dang‐Khoa Nguyen (Reviews in Aquaculture, 2019)
The paper explores the trade competitiveness of seven major shrimp‐exporting countries, namely Vietnam, China, Thailand, Ecuador, India, Indonesia and Mexico, to the United States. Specifically, we investigate whether the US antidumping petitions have an impact on the bilateral revealed comparative advantage ( RCA ) indexes for each of the seven shrimp‐exporting countries with the United States. Monthly data from January 2003 to December 2014 and a panel data model are used to examine the determinants of the RCA for the shrimp‐exporting countries. The empirical results show the shrimp‐exporting countries have superior competitiveness against the shrimp market in the United States. Moreover, the RCA indexes are significantly negatively influenced by shrimp prices, and are positively affected by US income per capita. However, the EMS (Early Mortality Syndrome) shrimp disease, domestic US shrimp quantity, exchange rates and US antidumping laws are found to have no significant impacts on the RCA indexes. In terms of policy implications, the United States should try to reduce production costs of shrimp in the US market instead of imposing antidumping petitions. Moreover, the shrimp‐exporting countries should try to maintain their comparative advantage and diversify into new markets.

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

CLDN6 enhances chemoresistance to ADM via AF-6/ERKs pathway in TNBC cell line MDAMB231 - Minlan Yang; Yanru Li; Yang Ruan; Yan Lu; Dongjing Lin; Yinping Xie; Bing Dong; Qihua Dang; Chengshi Quan (Molecular and Cellular Biochemistry, 2018)

Effect of Cu(II) on the stability of oxyanion-substituted schwertmannite - Junfei Li; Yingying Xie; Guining Lu; Han Ye; Xiaoyun Yi; John R. Reinfelder; Zhang Lin; Zhi Dang (Environmental Science and Pollution Research, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Fast trace determination of nine odorant and estrogenic chloro- and bromo-phenolic compounds in real water samples through automated solid-phase extraction coupled with liquid chromatography tandem mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-xian Lian; Chuang-tao Yang; Qing Lin; Hua Yin; Zhang Lin; Zhi Dang (Environmental Science and Pollution Research, 2018)

Bioremediation of PAH-contaminated farmland: field experiment - Lin Ma; Fucai Deng; Chen Yang; Chuling Guo; Zhi Dang (Environmental Science and Pollution Research, 2018)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Effects of modified biochar on rhizosphere microecology of rice (Oryza sativa L.) grown in As-contaminated soil - Shusi Liu; Yixin Lu; Chen Yang; Chuanping Liu; Lin Ma; Zhi Dang (Environmental Science and Pollution Research, 2017)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)

Methylmalonate‐semialdehyde dehydrogenase mediated metabolite homeostasis essentially regulate conidiation, polarized germination and pathogenesis in Magnaporthe oryzae - Justice Norvienyeku; Zhenhui Zhong; Lili Lin; Xie Dang; Meilian Chen; Xiaolian Lin; Honghong Zhang; Wilfred M. Anjago; Lianyu Lin; Waheed Abdul; Zonghua Wang (Environmental Microbiology, 2017)
Summary Plants generate multitude of aldehydes under abiotic and biotic stress conditions. Ample demonstrations have shown that rice‐derived aldehydes enhance the resistance of rice against the rice‐blast fungus Magnaporthe oryzae . However, how the fungal pathogen nullifies the inhibitory effects of host aldehydes to establish compatible interaction remains unknown. Here we identified and evaluated the in vivo transcriptional activities of M. oryzae aldehyde dehydrogenase (ALDH) genes. Transcriptional analysis of M. oryzae ALDH genes revealed that the acetylating enzyme Methylmalonate‐Semialdehyde Dehydrogenase (MoMsdh/MoMmsdh) elevated activities during host invasion and colonization of the fungus. We further examined the pathophysiological importance of MoMSDH by deploying integrated functional genetics, and biochemical approaches. MoMSDH deletion mutant Δ Momsdh exhibited germination defect, hyper‐branching of germ tube and failed to form appressoria on hydrophobic and hydrophilic surface. The MoMSDH disruption caused accumulation of small branch‐chain amino acids, pyridoxine and AMP/cAMP in the Δ Momsdh mutant and altered Spitzenkörper organization in the conidia. We concluded that MoMSDH contribute significantly to the pathogenesis of M. oryzae by regulating the mobilization of Spitzenkörper during germ tube morphogenesis, appressoria formation by acting as metabolic switch regulating small branch‐chain amino acids, inositol, pyridoxine and AMP/cAMP homeostasis.

Effects of genetic variants of the bovine WNT8A gene on nine important growth traits in beef cattle - Yong-Zhen Huang; Yong Zou; Qing Lin; Hua He; Li Zheng; Zi-Jing Zhang; Yong-Long Dang; Chu-Zhao Lei; Xian-Yong Lan; Xing-Shan Qi; Hong Chen (Journal of Genetics, 2017)

Three-dimensional tomography using high-power induced polarization with the similar central gradient array - Jun-Lu Wang; Pin-Rong Lin; Meng Wang; Dang Li; Jian-Hua Li (Applied Geophysics, 2017)

Simultaneous determination of estrogenic odorant alkylphenols, chlorophenols, and their derivatives in water using online headspace solid phase microextraction coupled with gas chromatography-mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-Xian Lian; Chuangtao Yang; Qing Lin; Hua Yin; Zhi Dang (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Applications of Savitzky-Golay Filter for Seismic Random Noise Reduction - Yanping Liu; Bo Dang; Yue Li; Hongbo Lin; Haitao Ma (Acta Geophysica, 2016)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Spectral response of different eroded soils in subtropical china: A case study in Changting County, China - Chen Lin; Sheng-lu Zhou; Shao-hua Wu; Qing Zhu; Qi Dang (Journal of Mountain Science, 2014)

Molecular characterization of putative biocorroding microbiota with a novel niche detection of Epsilon ‐ and Zetaproteobacteria in Pacific Ocean coastal seawaters - Hongyue Dang; Ruipeng Chen; Lin Wang; Sudong Shao; Lingqing Dai; Ying Ye; Lizhong Guo; Guiqiao Huang; Martin G. Klotz (Environmental Microbiology, 2011)
Summary Submerged metal surfaces in marine waters undergo rapid microbial colonization and biocorrosion, causing huge damage to marine engineering facilities and significant financial losses. In coastal areas, an accelerated and particularly severe form of biocorrosion termed accelerated low water corrosion (ALWC) is widespread globally. While identification of biocorroding microorganisms and the dynamics of their community structures is the key for understanding the processes and mechanisms leading to ALWC, neither one is presently understood. In this study, analysis of constructed clone libraries and qPCR assays targeting group‐specific 16S rRNA or functional marker genes were used to determine the identity and abundance of putative early carbon steel surface‐colonizing and biocorroding microbes in coastal seawater. Diverse microbial groups including 10 bacterial phyla, archaea and algae were found to putatively participate in the surface‐colonizing process. Analysis of the community structure of carbon steel surface microbiota revealed a temporal succession leading to ALWC. By extending the current state of knowledge, our work demonstrates the global importance of Alphaproteobacteria (mainly Rhodobacterales ), Gammaproteobacteria (mainly Alteromonadales and Oceanospirillales ), Bacteroidetes (mainly Flavobacteriales ) and microalgae as the pioneer and sustaining surface colonizers that contribute to initial formation and development of surface biofilms. We also discovered Epsilonproteobacteria and the recently described Zetaproteobacteria as putative corrosion‐causing microorganisms during early steps of the ALWC process. Hence, our study reports that Zetaproteobacteria may be ubiquitous also in non‐hydrothermal coastal seawaters and that ALWC of submerged carbon steel surfaces in coastal waters may involve a highly diverse, complex and dynamic microbial consortium. Our finding that Epsilon ‐ and Zetaproteobacteria may play pivotal roles in ALWC provides a new starting point for future investigation of the ALWC process and mechanism in marine environments. Further studies of Epsilon ‐ and Zetaproteobacteria in particular may thus help with the design of effective corrosion prevention and control strategies.

Response surface optimization of dissolved oxygen and nitrogen sources for the biodegradation of MTBE and BTEX - Chi-Wen Lin; Chia-Hsien Yen; Hung-Chun Lin; Dang-Thuan Tran (Biodegradation, 2010)

Note: Anti-viral activity ofAilanthus altissima crude extract onRice stripe virus in rice suspension cells - J. G. Yang; Y. G. Dang; G. Y. Li; L. J. Guo; W. T. Wang; Q. W. Tan; Q. Y. Lin; Z. J. Wu; L. H. Xie (Phytoparasitica, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Screening and identification of vascular-endothelial-cell-specific binding peptide in gastric cancer - Shuhui Liang; Tao Lin; Jie Ding; Yanglin Pan; Dongmei Dang; Changcun Guo; Min Zhi; Pengtao Zhao; Li Sun; Liu Hong; Yongquan Shi; Liping Yao; et al. (Journal of Molecular Medicine, 2006)

The Stability and Existence Condition of Nonlinear Travelling Wave Solution in Basic Uniform Flow - Y. Xu; Z. Lin; R. Dang (Meteorology and Atmospheric Physics, 1999)